Impacts of Climate Change on Wastewater Systems in Reykjavík - Ásta Ósk Hlöðversdóttir 1982- (2011)
Due to climate change, precipitation is projected to increase in Northern Europe (Bates et. al., 2008). Such changes can influence the design and management of wastewater systems. Most of the current climate change studies have not analyzed short duration precipitation which is needed for wastewater system design. The objectives of this project are first to investigate whether changes in short duration extreme precipitation have occurred in Reykjavík in the past decades, then to assess increased flood risk in the wastewater system in downtown Reykjavík using the Mike Urban simulation program. No significant precipitation trends were found on an annual basis. A positive significant trend of 0.12mm/decade, was found in August (10 minutes duration) and a negative trend of -0.08 mm/decade was found in November. The times series analysis also revealed the presence of decadal to multi-decadal variations related to natural climate variability, which may have counteracting effects on long-term trend detection, as the variations could be larger in magnitude than potential trends. By updating the 1M5 method, used for Icelandic wastewater system design, with new data (1985-2008), 10 minutes design intensity increased by 16%. Flooding in downtown Reykjavík was analyzed using both an 11 year long time series from a digital rain gauge, and Chicago design storms with intensity with a 5 year return period. Three scenarios were analyzed, firstly current design practice, secondly current situation, and thirdly a 20 % increase. Number of sensitive areas were identified, and already 20% of the system is under pressure for an event with a 5 year return period. The effects of densifications were also investigated, revealing that a 10% increase in runoff coefficient could increase floods by 35%. Umhverfis- og orkurannsóknasjóður Orkuveitu Reykjavíkur